A comparative analysis of the post‐cranial skeleton of fossorial and non‐fossorial gymnophthalmid lizards. (18th March 2013) - Roscito, Juliana G.; Rodrigues, Miguel T.
<x xml:space="preserve">Abstract</x> Squamates are found in a wide range of habitats and show a corresponding diversity of morphologies that can often be correlated with locomotor mode. The evolution of a snake‐like body form, frequently associated with fossoriality, from a typical lacertiform morphology involves changes in the morphology of vertebrae, girdles, and limbs; the changes are mainly manifested by the reduction or loss of limbs and body elongation. In this study, we describe the axial and appendicular skeletons of six closely related gymnophthalmid species. Three of them show a lizard‐like morphology, with a four‐digit forelimb and a five‐digit hindlimb, and the other three show a snake‐like morphology associated with a burrowing habit, with reduced limbs and a longer body in comparison to the former three species. We show that vertebral morphology is similar among the six species, with the differences being accounted for by an increase in the number of vertebrae and by the structural reduction of girdles and limbs in the snake‐like species. Skeletal morphology provides valuable information on locomotion type, physiology, diet, and other biological features. The burrowing morphology usually involves accentuated reduction of girdle and limb elements, reflecting an undulating type of locomotion in which the limbs play little or no role in propelling the body; in contrast, well‐developed limbs and girdles indicate a greater reliance on the limbs for body propulsion. Limb reduction is frequent among vertebrates, but many different phenotypes are found in species exhibiting some kind of reduction, indicating that different mechanisms and evolutionary pressures may be involved in generating the diverse morphologies. J. Morphol. 274:845–858, 2013. © 2013 Wiley Periodicals, Inc.